2021
DOI: 10.3390/foods10010197
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Antioxidant Activity of Pumpkin Polysaccharide (Cucurbita moschata Duchesne ex Poiret) Modified by Subcritical Water

Abstract: In this paper, subcritical water (SCW) was applied to modify pumpkin (Cucurbita moschata Duchesne ex Poiret) polysaccharides, and the properties and antioxidant activity of pumpkin polysaccharides were investigated. SCW treatments at varying temperature led to changes in the rheological and emulsifying properties of pumpkin polysaccharides. SCW treatments efficiently degraded pumpkin polysaccharides and changed the molecular weight distribution. Decreases in intrinsic viscosity, viscosity-average molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 61 publications
(71 reference statements)
1
11
0
Order By: Relevance
“…In general, W-CCPs, RPP-3, and RPP-4, which have stronger antioxidant activity, also have better α-glucosidase and α-amylase inhibitory activities. According to previous reports, similar results have been observed that extracted or molecularly modified pumpkin polysaccharides have better in vitro antioxidant and hypoglycemic activities (9)(10)(11)(12). The nonpurified pumpkin polysaccharides (WA-CCPs, DPPs), which were extracted by hot water extraction and water extraction and alcohol precipitation, have lower in vitro antioxidant and hypoglycemic activities than the hot water-extracted pumpkin polysaccharide, W-CCPs.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In general, W-CCPs, RPP-3, and RPP-4, which have stronger antioxidant activity, also have better α-glucosidase and α-amylase inhibitory activities. According to previous reports, similar results have been observed that extracted or molecularly modified pumpkin polysaccharides have better in vitro antioxidant and hypoglycemic activities (9)(10)(11)(12). The nonpurified pumpkin polysaccharides (WA-CCPs, DPPs), which were extracted by hot water extraction and water extraction and alcohol precipitation, have lower in vitro antioxidant and hypoglycemic activities than the hot water-extracted pumpkin polysaccharide, W-CCPs.…”
Section: Discussionsupporting
confidence: 73%
“…Pumpkin (Cucurbita moschata) is one of the most popular vegetables in the world, and it contains carotenoids, pectin, dietary fiber, mineral elements, polysaccharides, para-aminobenzoic acid, sterols, proteins, and peptides. At present, researchers have shown that pumpkin polysaccharides can be used as potential hypoglycemic substances and have certain therapeutic effects on diabetes (4)(5)(6)(7)(8), antioxidant activity (4,(9)(10)(11)(12), lowering plasma lipids (8), improving immunity (9), and anti-cancer (13). Currently, studies on in vitro hypoglycemic activity in pumpkin polysaccharides mainly focus on radical-scavenging ability assay, plasma iron reduction ability assay, α-glucosidase and α-amylase inhibition assay, bile acid binding ability assay, and pancreatic islet β-cell damage protective ability assay (4,9,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of Mw for such polysaccharides enhanced antioxidant activities, including radical scavenging activity and reducing power. Q. Li's group proposed that reduction of Mw resulted in the exposure of more reducing ends for such polysaccharides (Yu et al., 2021 ). Thus, the high ROS and reactive nitrogen species (RNS) radical scavenging activities we observed for M‐DOP may have been due to decreased Mw and increased exposure of reducing ends.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute value of WPINs–SW–PE on the zeta potential was greater than that of WPINs–H–PE on the zeta potential. Interestingly, both of them were greater than 30 mV, indicating that WPINs treated with both SW and hydrothermal methods could enhance the stability of PE [ 52 ]. Based on these results, SW treatment may reduce the average particle size and increase the zeta potential of PE, which was attributed to the increase in the surface charge and distribution of WPINs during SW. WPINs–SW–PE will act as a higher and more stable encapsulation rate during the subsequent encapsulation of Cur.…”
Section: Resultsmentioning
confidence: 99%